Clinical outcome of 115 patients with synchronous bilateral Wilms’ tumor: largest cohort of single-center experience - Asfour, Hosam Y.; Zekri, Wael; Hussein, M. Hany; Elkinaai, Naglaa; Sobhy, Sarah; Helmy, Mahmoud M.; Nasr, Azza; Refaat, Amal; Gamal, Rana; Younes, Alaa; El-Ayadi, Moatasem; Khalil, Sahar A. (Frontiers in Oncology, 2025)
IntroductionBilateral Wilms’ tumor (BWT) represents 5 – 8% of patients with Wilms’ tumor (WT). Despite the improvement of WT survival, still patients with BWT are challenging with a high risk of relapse and renal failure.PurposeTo assess the outcome of pediatric patients with BWT treated at Children’s Cancer Hospital Egypt (CCHE) 57357, and to assess the long-term nephrotoxicity among these patients.MethodsThis was a retrospective study including all patients with synchronous BWT treated at CCHE 57357 from 2007 until 2020. Records of all patients were reviewed. Patients were followed up until end of December 2024.ResultsIn 115 eligible patients, median age was 31.5 months (range 3 month – 9 years). Male to female ratio was 1:1.67. Abdominal mass was the most common presentation (69.5%). At the end of the study, 5-year EFS and OS were 69% and 76.7%. Patients with high-risk pathology had the worst prognosis regarding EFS and OS, keeping its significance in uni- and multivariate analyses as the factor with highest hazard ratio (HR = 2.931, 95% CI 1.366 - 6.289 p 0.006). Out of 29 events related to the disease, 21 included local progression/relapse (72.5%), and 8 lung progression/relapse (27.5%). The incidence of ESRD was 6.9% (8 patients).ConclusionBilateral Wilms’ tumor poses a significant challenge all over the world. Proper timing and type of surgery should be tailored according to each patient. Low-middle income countries face additional challenges related to supportive care for those children who usually present at a very young age with a tangible proportion of them requiring regular hemo dialysis and occasionally renal transplantation.